2017
DOI: 10.1111/aos.13355
|View full text |Cite
|
Sign up to set email alerts
|

The physical properties of generic latanoprost ophthalmic solutions are not identical

Abstract: Generic latanoprost eye drops should not be considered identical to the original brand version as regards to drop size, volumes, pH values, buffer capacity, viscosity, hardness of bottles and costs. It is likely that these issues affect compliance and intraocular pressure (IOP)-lowering effect. Therefore, re-evaluation of the requirements for introducing generic eye drops seems reasonable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 20 publications
0
13
0
2
Order By: Relevance
“…Excipients are heterogenous inert pharmaceutical ingredients used in product formulations, for example, thickening agents and buffers. In most cases, they have limited or no pharmacological activity, but they can influence drug stability and bioavailability and these differences have the potential to affect efficacy [25,26]. Kolko and colleagues examined the physical properties of 5 generic latanoprost solutions and found substantial differences to the branded version [26].…”
Section: Tolerability and Differences In Formulationmentioning
confidence: 99%
See 3 more Smart Citations
“…Excipients are heterogenous inert pharmaceutical ingredients used in product formulations, for example, thickening agents and buffers. In most cases, they have limited or no pharmacological activity, but they can influence drug stability and bioavailability and these differences have the potential to affect efficacy [25,26]. Kolko and colleagues examined the physical properties of 5 generic latanoprost solutions and found substantial differences to the branded version [26].…”
Section: Tolerability and Differences In Formulationmentioning
confidence: 99%
“…Whereas the packaging of innovator products is carefully designed and evaluated in clinical trials, aiming to identify issues with bottle design, the same is not true of generic eye drops. Several studies have shown considerable variation in the force required to squeeze different bottles and successfully release a drop [26,33,34]. For example, Kolko and colleagues reported a considerable difference in force was needed to expel drops from a bottle of Xalatan compared to different generic latanoprost bottles, with Xalatan requiring the least pressure [26].…”
Section: Adherence and Ease Of Usementioning
confidence: 99%
See 2 more Smart Citations
“…Кроме того, изменение цвета и формы может запутать пациентов и тем самым повлиять на их приверженность лечению [19][20][21]. Исследователи из Дании M. Kolko и J. Koch [22] сравнили физические параметры оригинального препарата Ксалатан и пяти дженериков латанопроста. Полученные результаты показали значительное различие в размерах капель и количестве капель в пузырьках.…”
Section: Issues Of Safety and Efficacy Of Drugs Attracts Much Attentiunclassified